2014
DOI: 10.1021/am505202p
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Surface Deoxidation Using Strontium Oxide Deposited with the Pulsed Laser Deposition Technique

Abstract: The epitaxial growth of functional oxides on silicon substrates requires atomically defined surfaces, which are most effectively prepared using Sr-induced deoxidation. The manipulation of metallic Sr is nevertheless very delicate and requires alternative buffer materials. In the present study the applicability of the chemically much more stable SrO in the process of native-oxide removal and silicon-surface stabilization was investigated using the pulsed-laser deposition technique (PLD), while the as-derived su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…The Sr/La, Mn/La, and O/La ratios are increasing from 973 to 1023 K, which can be attributed to the crystallization of LSMO, as discussed in the XRD and AFM results. The Sr/La ratio has almost no change from 1023 to 1073 K but decreases linearly from 1073 to 1173 K, indicating that desorption and deoxidation processes of the segragated SrO are occurring [41]. The O/La ratios increase from 1023 to 1073 K due to the formation of SrO from segregated strontium [31].…”
Section: Resultsmentioning
confidence: 99%
“…The Sr/La, Mn/La, and O/La ratios are increasing from 973 to 1023 K, which can be attributed to the crystallization of LSMO, as discussed in the XRD and AFM results. The Sr/La ratio has almost no change from 1023 to 1073 K but decreases linearly from 1073 to 1173 K, indicating that desorption and deoxidation processes of the segragated SrO are occurring [41]. The O/La ratios increase from 1023 to 1073 K due to the formation of SrO from segregated strontium [31].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it has been demonstrated that STO grown on a graphene buffer layer on silicon has a dominant (00 l ) orientation, but coexisting with a small portion of (110)-, (111)-, and (211)-oriented grains. 26 In this work, we employ SrO to deoxidize the uncovered Si surface before STO deposition, 33 which plays a key role in inducing (001) single oriented growth of STO on rGO. The details will be presented in a separate publication.…”
Section: Resultsmentioning
confidence: 99%
“…To deoxidize the Si surface uncovered by rGO and achieve a (001) single oriented growth of STO, 15 pulses of SrO were first deposited using a laser fluence of 2 J/cm 2 and a frequency of 0.1 Hz. 33 After flash annealing at 840 °C for 2 min, the sample was cooled down to 760 °C and 40 nm STO was deposited in high vacuum with a laser fluence of 2 J/cm 2 and a frequency of 3 Hz. RHEED patterns recorded during the growth of SrO and STO can be found in Figure S3 of the Supporting Information.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…This model assumes, aside from STO and interface layers, an additional Si layer with less density than the substrate, in order to simulate possible ion implantation due to the energetic nature of the PLD deposition. 3 For the interface layer, strontium silicates (SrSiO 3 and Sr 2 SiO 4 ) and silicon oxides were tested: the best results were obtained using a strontium silicate, with no denite improvements found when one of them was used over the other. A model without this interface layer was also tested, but the ttings quality decreased noticeably.…”
Section: Interfacementioning
confidence: 99%